Recruitment, Retention, and Succession Planning for District Health Directors - Lee Rudd (Journal of the Georgia Public Health Association, 2017)
Background: Since the District Health Director (DHD) leads the district health organization, plans must be put in place to ensure that we retain current directors and anticipate the future when the DHD retires from the position. Methods: Best practices in the areas of recruiting, retention, and succession planning are used to present resolutions to the problems. Results: By following the steps identified in the best practices, there is a reasonable chance that the district will be prepared for any change in leadership. Conclusions: Using the best practices identified by human resources professionals combined with the unique characteristics of public health districts will ensure success. Key words: management, public health professionals